Communication technology update and fundamentals - Grant, August E., 1956-; Meadows, Jennifer Harman (Routledge, 2018)
For three decades, Communication Technology Update and Fundamentals has set the standard as the single best resource for students and professionals looking to brush up on how communication technologies have developed, grown, and converged, as well as what's in store for the future. The secret to the longevity is simple--every two years, the book is completely rewritten to ensure that it contains the latest developments in mass media, computers, consumer electronics, networking, and telephony. Plus, the book includes the Fundamentals: the first five chapters explain the communication technology ecosystem, the history, structure, and regulations. The chapters are written by experts who provide snapshots of the state of each individual field. Together, these updates provide a broad overview of these industries, as well as the role communication technologies play in our everyday lives. In addition to substantial updates to each chapter, the 16th edition includes:First-ever chapters on Virtual/Augmented Reality and eSports. Overview of industry structure, including recent and proposed mergers and acquisitionsSuggestions on how to get a job working with the technologies discussed. The companion website, www.tfi.com/ctu, offers updated information on the technologies covered in this text, as well as links to other resources. Updated user data in every chapter.